The world anti-doping program and the primary care physician - Hilderbrand, R. L. (Pediatric Clinics of North America, 2007)
The presence of a prohibited substance in an athlete's urine (or blood, when applicable) or the use of a prohibited method constitutes a doping offense, even if the substance is a pharmaceutical and is properly prescribed. To avoid a doping offense for the therapeutic use of a prohibited substance or method the International Standard for Therapeutic Use Exemptions (TUE) must be followed. When the TUE is required, the appropriate process must be completed before testing under conditions where the substance or method is prohibited. This article describes the World Anti-Doping Code and the International Standards, which are part of the Code. In addition, the procedures for the proper preparation and submission of TUE requests are presented along with the manner in which the requests are considered by the Therapeutic Use Exemption Committees.